Compensatory and Rehabilitative Cognitive Training Improves Executive Functions and Metacognition - Husseini, zahra; Nejati, vahid; Habibi, Mojtaba (Iranian Journal of Educational Sociology, 2022)
Purpose: The main objective of the present paper is to boost executive functions and meta-cognition via compensatory and rehabilitative cognitive training.Methodology: In a randomized controlled trail with pretest, post-test and follow-up assessment, the effects of compensatory and rehabilitative cognitive training via education and personalized practice was studied on the EF and metacognition of 126 secondary students aged 16-18. Participants were assigned randomly into an experimental training group (n=61) using Practical Cognitive Strategy Training (PCST) or a wait-list control group (n=65). PCST (Roshd) consisted of two parts: cognitive strategy awareness and practice for compensatory cognitive training and cognitive exercises for rehabilitative cognitive training. The data was analyzed using repeated measure ANOVA in SPSS 23.Findings: Results showed a significant difference between experimental and control group in strategy use after twelve sessions of training once a week in a twelve-week period of training and a one-month follow-up assessment (P≤0.001). The participants also reported some kinds of transfer in the use of learned cognitive strategies to other life activities. Limitations: The study only used practical real life executive functions exercises and let the students choose whether to use training apps or not. The amount of extra training out of training situation was not controlled.Conclusion: Practical daily-life-based executive functions training can practically enhance executive functions and meta0cognitipon in real life activities.